Good prenatal detection rate of major birth defects in HIV‐infected pregnant women in Italy. (6th November 2015) - Floridia, M.; Mastroiacovo, P.; Ravizza, M.; Todros, T.; Chiadò Fiorio Tin, M.; Marconi, A. M.; Cetin, I.; Maruotti, G. M.; Liuzzi, G.; Pinnetti, C.; Degli Antoni, A.; Spinillo, A.; et al.
Abstract : What's already known about this topic? Exposure to antiretroviral treatment in pregnancy does not seem to increase the risk of birth defects, but there is no information on the rate of prenatal detection of such defects. What does this study adds? We provide for the first time, in a national case series, information about prenatal detection rate in women with HIV (51.6% for any major defect, 66.7% for chromosomal abnormalities, and 85% for severe structural defects).